MARKETING TOOL FOR EVALUATING THE VALUE OF THE PRODACT IN TNE PRACTICE OF PROJECT MANAGEMENT - Дзюба, Тамара Владимировна; Данченко, Елена Борисовна (Eastern-European Journal of Enterprise Technologies, 2013)
During the financial crisis, creating a successful commercial product is not a pleasant surprise, but the result of a comprehensive and systematic analysis and monitoring of marketing risks leading to a failure to achieve planned business results and as a consequence, the failure to achieve the objectives of the project stakeholders. Marketing risks of innovative projects can be reduced or minimized by the project of creating a product that best meet the expectations of the ultimate consumer. This paper discusses the application of the concept multi attributive model to estimate the value of the goods of the product of the project in terms of the end user. Using this model allows testing of an innovative product to its market launch. Testing phase is well implemented in IT-projects, but in real projects in the consumer sector is often ignored. The result of this approach is the increasing marketing project risks. This article proves, that the most important and critical in innovative projects can be considered - a marketing risk "of creating a product with a low perceived value." In order to prevent the occurrence of such risks, the authors proposed the usage of the concept model multi attributive product that allows you to see through the eyes of the consumer product innovation. This approach can be used in the development of consumer and industrial products.